Kontribusi Ekonomi Digital terhadap Pertumbuhan Ekonomi dan Penciptaan Lapangan Kerja di Indonesia - Gai, Maria Fernanda; Kope, Mariano H. K.; Seto, Cresensia M.; Dima, Enike Tje Yustin (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The rapid development of digital technology has transformed the economic landscape globally, yet its optimal impact in developing countries like Indonesia remains a challenge. This study aims to analyze the contribution of the digital economy to Indonesia's economic growth, identify key sectors with high employment potential, and formulate strategic responses to maximize its benefits. Employing a narrative literature review approach, the study synthesizes findings from peer-reviewed journals, institutional reports, and statistical data published over the last five years. The analysis reveals that Indonesia’s digital economy fueled by rising internet penetration, the growth of digital startups, and evolving consumer behavior has significantly contributed to national economic resilience, particularly during the COVID-19 pandemic. Sectors such as fintech, e-commerce, creative industries, and agriculture show strong potential for job creation and GDP contribution. However, several structural challenges persist, including unequal digital infrastructure, low digital literacy, and regulatory gaps. The study concludes that inclusive digital economic policies, combined with investments in digital infrastructure and workforce development, are essential to ensure sustainable growth and broader socio-economic impact. The digital economy is poised to become a cornerstone of Indonesia’s future economic model if properly integrated and equitably distributed.